Minimally invasive neurosurgery. II - Bauer, Bernhard L; Hellwig, Dieter (Springer, 1994)
In 1992 the Editors published the first volume of Minimally Invasive Neurosurgery (MIN I) which described the current state of the art in this rapidly developing field of neurosurgery and reported first clinical experiences with these new technologies. The subject of MIN II is limited to endoscopic anatomy, technical devices and surgical management of disorders suitable for endoscopic procedures. The indications and approaches in different diseases are still highly preliminary and longterm results are not yet available. The clinical value and the benefit to the patients treated with these new techniques must still be proven against the well established standards of microsurgery. This volume presents a critical update of neuroendoscopy.
Acta neurochirurgica, ISSN 0065-1419 suppl. 61, 1994
Keywords: neurochirurgie; Minimally Invasive Surgical Procedures; Radiosurgery; Neurosurgical Procedures; neurochirurgické výkony; miniinvazivní chirurgické výkony; radiochirurgie